Periapical repair after root canal filling with different root canal sealers - Tanomaru-Filho, Mário [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Leonardo, Mario Roberto [UNESP]; da Silva, Lea Assed Bezerra (FapUNIFESP (SciELO), 2009)
The aim of this study was to evaluate periapical repair after root canal filling with different endodontic sealers. Sixty four root canals from dog ́s teeth were filled, divided into 4 groups (n=16). Root canals were instrumented with K-type files and irrigated with 1% sodium hypochlorite solution. Root canals were filled in the same session by active lateral condensation of the cones and sealers: Intrafill, AH Plus, Roeko Seal and Resilon/Epiphany System. After 90 days, the animals were euthanized and the tissues to be evaluated were processed and stained with hematoxylin and eosin. For histopathological analysis, the following parameters were evaluated: inflammatory process, mineralized tissue resorption, and apical mineralized tissue deposition. Histopathological analysis demonstrated that Intrafill had less favorable results in terms of apical and periapical repair, compared to the other sealers (p<0.05). AH Plus, Roeko Seal, and Epiphany sealers had similar and satisfactory results (p>0.05). In conclusion, AH Plus and the materials Roeko Seal and Epiphany are good options for clinical use in Endodontics.
Keywords: Endodontics; Histopathological evaluation; Inflammation; Root canal filling material; root canal filling material; animal; dog; endodontics; materials testing; methodology; nonparametric test; tooth periapical disease; Animals; Dogs; Materials Testing; Periapical Periodontitis; Root Canal Filling Materials; Root Canal Obturation; Statistics, Nonparametric